Determinations of student enrolment in private higher learning institution: a study if UNIKL MITEC / Noor Azrina Rahmat, Siti Norhafizah Mohamed Safian & Ummi Ruqayah Abu Bakar - Rahmat, Noor Azrina; Mohamed Safian, Siti Norhafizah; Abu Bakar, Ummi Ruqayah (2021)
The higher education sector in Malaysia has grown in terms of quality and quantity. The continuous number in private universities is not supported by the number of students who planned to further their studies. The Malaysian government has allocated a large amount of fund under the Ministry of Education, which is the largest recipient in 2019 from total government expenditure, the allocation is for physical infrastructure, teaching and learning, research and even society. The lack of new students causes the university to rely entirely on feeders and students who are interested in continuing their studies. The perception on the period of study, the difficulty on the courses offered and location make students refuse to enroll into private university. This study uses the SWOT approach (Strength, Weaknesses, Opportunities and Threats) to analyze the issues at UniKL MITEC and several situations were found that relate to its current conditions. There are criteria that need to be evaluated by students when making decisions about future universities based on some of the alternatives offered by the institution. One of the factors is the registration rate achieved by each institution of higher learning (IPT) in each academic calendar year. The purpose of this research is to examine the important decision factors that influence students to make choices and enroll in institutions of higher learning. This study was conducted at a private institution of higher learning which is UniKL MITEC Pasir Gudang, Johor. A quantitative study was performed through the application of a questionnaire with student from first and final year Diploma student, alumni, individuals who want to further their study, and a total of 288 samples were collected. Through regression analysis, the findings show that financial considerations, campus attractiveness and academic quality play an important role in influencing student decisions when choosing higher education institutions. Respondents seemed to analyze each of the criteria that acts as an attractive factor and contributes to the selection process of choosing the university. In addition, this research examines how certain factors become criteria in the selection process. These findings allow the researchers to recommend the steps and strategies used by institutions of higher learning based on the needs and wants of students